ArCEs - A digital archive of Italian Colonial Cartography and Scientific Expeditions - Calloud, Irene; Zamperlin, Paola (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
ArcCEs is a study for developing a digital archive on Italian scientific expeditions in Northern and Eastern Africa and the former Italian colonies (19th–20th centuries). The aim of the project is to assess, protect and enhance an important corpus of documents (historical cartographies, photographs, scientific papers and archive documents) distributed among public archives and private collections. The database structure is based on the Dublin Core metadata standard. The information system is designed to integrate and make interoperable digital resources, to ensure standardized and complex indexing, and to support advanced retrieval, according to the standards in use. The geolocation of the resources in a GIS environment can display query results in the Google Earth environment.